Penilaian Tingkat Kestabilan Lereng Batuan Granit Menggunakan Metode Slope Mass Rating (SMR) dan Analisis Kinematika di PT Mandiri Karya Makmur: The Assesment of Granite Rock Slope Stability Using Slope Mass Rating (SMR) Method and Kinematic Analysis in PT Mandiri Karya Makmur - Mirsandi, Mirsandi; Irvani, Irvani; Fahraini, Ferra (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2017)
PT Mandiri Karya Makmur (MKM) was a private company that mine granite rock. Level in mine site was almost steep so that it had the possibility to failure. The study was conducted to assess the stability of rock slope that may endanger the safety of workers. This study to determine the quality of rock mass of slope based on the value of SMR (Slope Mass Rating) and kinematics analysis. The data used included UCS, RQD, Space of discontinuity, Discontinuity conditions, Groundwater conditions and Discontinuity orientation data. Slopes data were divided into 4 scanline based on the direction changing of the slope. To determine the type of failure using kinematics analysis of Dips program and Schmidt Net.The analysis results revealed that the quality of rock mass for scanline II was very good or very stable based on the SMR value. While on the rock mass quality of scanline I, III and IV were good with the stability of the slope was in a stable condition. The possibility of a failure in scanline I, III and IV were only several blocks. There were two blocks that has possibility to failure was on scanline III and IV. Estimation direction of slope failure on scanline III and IV respectively were N 1350 and N 1850 E. The supporting of slope instability can be done by scaling or cutting blocks that have potential to failure.